Jurassic palynostratigraphy of the Algarve Basin and the Carrapateira Outlier, Southern Portugal - Borges, Marisa (2011)
The Mesozoic Algarve Basin (AB) corresponds to the southernmost geological province of mainland Portugal. The Carrapateira Outlier (CO) is a small outcrop of Mesozoic rocks located 20 km north of the AB. In this study we investigated the palynology of the Jurassic (Upper Bajocian to Lower Kimmeridgian) of the AB and CO.